Green Human Resource Management On Sustainable Performance: The Mediating Role Of Digital Innovation - Tobing, Rudy; Nugroho, Dwiyanjana Santyo (LPPM ISNJ Bengkalis, 2024)
This study analyses the mediating role of digital innovation variables on the relationship between green human resource management (GHRM) and sustainability performance. This research method uses a mixed method, combining primary data in questionnaires and focus group discussions (FGD). This study also uses an experimental approach, which treats respondents, so the questionnaire is distributed to respondents 2 times. The findings of this study indicate that digital innovation can mediate the relationship between GHRM and sustainability performance. In addition, this study also proves that there is an increase in the role of digital innovation as a mediator after treatment compared to before treatment. This finding provides theoretical implications that GHRM can be supported by digital innovation so that it can be a reference for further research. This finding can be a reference for the government and start-up technology companies to accommodate the needs of companies in implementing GHRM. This is important because the starting point for companies to perform sustainability is to equip employees to be aware of the importance of the environment and sustainability.